The Influence of Motivation, Organizational Commitment, and Organizational Justice on Organizational Citizenship Behavior of the Municipal Police in East Lombok (Global Journal of Management and Business Research, 2020)
Municipal police organizations function realization of East Lombok yet to be declared maximum because there are many dimensions to the realization of less than one hundred percent. Believed to shape the organizational citizenship behavior (OCB) will improve the performance of individual members and organizations. Factors that must be addressed is through the management motivation, organizational commitment and organizational justice. The focus of this study was formulated three objectives in the form of motivational factors of significance to the OCB, the significance of organizational commitment on OCB and significance of organizational justice against OCB members of municipal police in East Lombok. The design of this research is associative research, established through analysis used partial least square (PLS). The process of data input by the number of observational data of 180 peoples, successfully formed outer and inner models.
Keywords: OCB; motivation; organizational commitment; and organizational justice